The associated factors non-compliance of rabies post exposure vaccination among dog bites patients in Perlis - Basir, Mohammad Fazrul Mohammad (2021)
Background: Thousands of people succumbed to dog-mediated human Rabies, and billions of USD economic lost have been reported. Rabies Post Exposure Vaccination (RPEV) remains the most fundamental and effective prevention of human Rabies if administered in a timely and appropriate manner. Non-compliance of the vaccination series is mainly reported because of the cost incurred for the vaccine, but that shall not happen in Malaysia. The recent canine Rabies outbreak in Perlis takes away the status of the free-Rabies country. Thus, it is vital to identify the factors associated with the non-compliance towards RPEV in Perlis in achieving zero dog-mediated human Rabies death by 2030. Objectives: To determine the proportion and associated factors for non-compliance of RPEV among dog bite patients between 2015 - 2020 in Perlis. Methodology: This is a retrospective cohort study using Perlis Rabid Potential Animal Bite Registry. Dog bite patients registered between July 2015 to June 2020 were selected for the sample. Descriptive analyses utilised to describe the sociodemographic while logistic regression used to determine the factor associated with non-compliance of RPEV. Non-compliance of RPEV define as the dog bite patient who discontinued the vaccination at any point during the recommended course without a medical reason. Results: The proportion of non-compliance for RPEV in Perlis from July 2015 till June 2020 was 19.5% (95% confidence interval (CI): 16.1,23.0) based on the analysis on 507 dog bite patient's data that fulfil the criteria for sample selection. Multiple logistic regression analysis shown that Siamese has significantly two-times (Adjusted Odd Ratio (Adj. OR): 2.00; 95% CI: 1.06,3.76; p-value = 0.031) odd higher to become non-compliance and being bitten during 3rd (Adj. OR: 0.27; 95% CI: 0.12,0.59; p-value = 0.001), 4th (Adj. OR: 0.24; 95% CI: 0.11,0.52; p-value < 0.001) and 5th (Adj. OR: 0.20; 95% CI: 0.09,0.44, p-value < 0.001) year of the outbreak has significantly lower odds to non-comply with RPEV. Conclusions: Despite the vaccine were available, accessible, and affordable most of the time to obtain in Malaysia, and there was still a portion (19.5%) in Perlis that did not comply with the RPEV series leads to a higher risk to develop human Rabies. Siamese ethnicities and dog bite patients who bitten at the beginning of outbreaks were more likely to receive incomplete RPEV.